Capacity Limits of Basic Turbo-Roundabouts - Kocianova, Andrea (Communications - Scientific letters of the University of Zilina, 2016)
Turbo-roundabouts with their specific design characteristics have become a suitable solution of a single-lane roundabouts capacity problem and a standard two-lane roundabouts safety problem. There is no doubt that turbo-roundabouts ensure a higher level of traffic safety in comparison to standard two-lane roundabouts due to a reduction of both conflict points and driving speed through the turbo-roundabouts. The question is if turbo-roundabouts can provide the same or a higher capacity than standard two-lane roundabouts. The answer, in the form of some important results of the basic turbo-roundabout total capacity at various traffic conditions and also in comparison with standard two-lane roundabouts, is presented in the paper. The capacity model is based on the gap-acceptance theory. Driver behaviour characteristics have been respected according to the Slovak technical guidelines. Redistribution of traffic flows into two lanes at entries and circulatory carriageway of roundabouts has been considered in the capacity calculations. An effective use of both lanes (left and right) has been assumed only at basic turbo-roundabout major entries. By contrast, low use of inner (left) lanes by drivers at entry and circulatory carriageway corresponding with real conditions in some countries has been assumed in the standard two-lane roundabout capacity calculations.